2013
DOI: 10.1002/acr.21846
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Subarachnoid Hemorrhage in Patients With Systemic Lupus Erythematosus: A Nationwide Population‐Based Study

Abstract: Objective. A relatively common occurrence of spontaneous subarachnoid hemorrhage (SAH) in patients with systemic lupus erythematosus (SLE) has been noted; however, the subsequent studies were conflicting. This nationwide populationbased study aimed to evaluate the risk of SAH in patients with SLE. Methods. We identified 16,967 SLE patients from the Taiwan National Health Insurance (NHI) database between 2000 and 2006, and compared the incidence rate of SAH with 16,967 randomly selected age-and sex-matched non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“… 18 Three examined subarachnoid haemorrhage separately. 14 19 20 Six studies presented estimates for ischaemic stroke, 13 15 17 18 20 21 one of which included the ICD-9 code for subarachnoid haemorrhage (ICD-9 430) in the ischaemic stroke outcome. 17 Liou et al investigated the risk of intracerebral haemorrhage; they did not give the number of events or subtype-specific HR, and only reported that the finding was non-significant.…”
Section: Resultsmentioning
confidence: 99%
“… 18 Three examined subarachnoid haemorrhage separately. 14 19 20 Six studies presented estimates for ischaemic stroke, 13 15 17 18 20 21 one of which included the ICD-9 code for subarachnoid haemorrhage (ICD-9 430) in the ischaemic stroke outcome. 17 Liou et al investigated the risk of intracerebral haemorrhage; they did not give the number of events or subtype-specific HR, and only reported that the finding was non-significant.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that these drugs can cause hypertension as a side effect [7,8,21], which could result in aneurysm formation and rupture, and therefore, could be one of the explanations for the higher rate of SAH in SLE patients. This hypothesis is also supported by the fact that higher daily steroid use (>10 mg) has been reported as an independent risk factor for increased incidence of SAH [4,9].…”
Section: Etiology Of Sah In Sle Patientsmentioning
confidence: 62%
“…It seems that in some populations, older age, high dose (>10 mg daily) steroid intake, and previous transfusions of red blood cells or platelets are independent risk factors for SAH [4,34].…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subarachnoid hemorrhage (SAH) is rare in patients with systemic lupus erythematosus (SLE), but more common than in the general non‐SLE population . Although the pathogenesis of SAH in patients with SLE remains poorly understood, aneurysm is known to be the most common cause.…”
Section: Introductionmentioning
confidence: 99%